Análisis presupuestario del Gobierno Autónomo Descentralizado Municipal del Cantón Calvas correspondiente al periodo 2018 Y 2019 - Rueda Castillo, Lutgarda Marisol (2020)
The Municipal GAD of the Cantón Calvas is a public institution of administrative and financial autonomy that aims to project, manage and execute its own resources to meet all the needs of citizens. One of the main objectives is: To promote development and contribute to the well-being of the community (social projects, works, improvement of community services and its surrounding areas). Guaranteeing the national plan of good living through the application of laws, regulations and public policies, which are governed by means of their powers as indicated by the Organic Code of Territorial Organization, Autonomy and Decentralization. The research was carried out according to the research subline: Financial Management, Tax and Social Commitment, with the topic: Budget Analysis of the Autonomous Decentralized Municipal Government of the Calvas canton corresponding to the period 2018 and 2019. Consisting of determining and analyzing the factors that They intervene in the activities carried out by the Administrative Management of the Institution. Where the two periods were analyzed, resulting in inconsistencies at the time of planning and executing them, since they do not make the projections according to the resources assigned within each year, keep in the budget schedules of income and expenses which was taken as reference two indicators: efficiency and effectiveness, to have a notion of the management of the accounting management carried out by the institution and through them to verify and analyze the level of fulfillment of the objectives and in addition to the administrative management.